DIAGNOSTIC ALGORITHM FOR MISSED ABORTION - Navruzova , R.S.; Mamajonova , N.Sh. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Introduction: Pregnancy, as a physiological condition, is a complex and insufficiently studied phenomenon. Even in a normal course, it involves major functional changes in almost all systems of the body, including the hemostasis system. Materials and Methods: A clinical-instrumental analysis was carried out among 128 pregnant women diagnosed with missed abortion. Data from anamnesis, physical examination, ultrasound scanning, and fetometry were collected. The cohort was divided into a retrospective group (n=78) and a primary group (n=50). Results: Most common findings included the disappearance of subjective pregnancy signs (76.4%), uterine size lagging behind gestational age (70.5%), and echographic signs of placental and chorionic changes. In 37.2% of patients, the absence of symptoms did not preclude the diagnosis, which was established solely based on sonographic imaging. Conclusion: The combination of ultrasound data with clinical evaluation enhances the accuracy of diagnosing missed abortion, particularly in asymptomatic cases. Early detection ensures timely intervention and prevents further complications.